2022
DOI: 10.3389/fimmu.2022.891570
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Expression of TLR2 in Aging Hearts Exacerbates Cardiac Inflammatory Response and Adverse Remodeling Following Ischemia and Reperfusion Injury

Abstract: This study tested the hypothesis that Toll-like receptor 2 (TLR2) augments the inflammatory responses and adverse remodeling in aging hearts to exacerbate myocardial injury and cardiac dysfunction.MethodsOld (20-22 months old) and adult (4-6 months old) mice of C57BL/6 wild-type and TLR2 knockout (KO) were subjected to coronary artery ligation (30 minutes) and reperfusion (3 or 14 days). Left ventricle function was assessed using a pressure-volume microcatheter. Cardiac infarct size was determined by histology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Our previous study found that the myocardium of old mice has higher level of TLR2 ( 13 ), and the present study confirmed this observation and identified elevated TLR2 levels in the liver and kidney. Based on these findings, we tested the hypothesis that elevated TLR2 levels augment inflammatory activity in sepsis and thereby results in worse cardiac dysfunction.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our previous study found that the myocardium of old mice has higher level of TLR2 ( 13 ), and the present study confirmed this observation and identified elevated TLR2 levels in the liver and kidney. Based on these findings, we tested the hypothesis that elevated TLR2 levels augment inflammatory activity in sepsis and thereby results in worse cardiac dysfunction.…”
Section: Discussionsupporting
confidence: 90%
“…Although TLR signaling is essential for host defense, persistent activation of TLRs, particularly TLR2, and related signaling pathways during sepsis would result in dysregulated systemic inflammatory responses ( 12 ). We observed in a previous study that aging elevates myocardial TLR2 levels ( 13 ), indicating that elevated TLR2 activity in aging heart augments myocardial inflammatory responses to sepsis. The current study tested the hypothesis that TLR2 plays a critical role in mediating myocardial inflammatory responses and cardiac dysfunction in old septic mice.…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…In addition, anti-apoA1 IgG could directly promote the endothelial expression of ICAM-1 and VCAM-1. Although the present study did not investigate underlying molecular mechanisms, previous publications showed that ICAM-1 and VCAM-1 expression is TLR2/TLR4-dependent ( 39 41 ), suggesting that the same innate immune receptors could be involved in anti-apoA1 IgG-induced trans-endothelial migration of immunocompetent cells. The impact of ART on auto-antibodies is poorly documented; however, the observation in our study is in line with the findings of Marinho and colleagues ( 42 ), who showed that the anti-retroviral nevirapine (NVP) was able to lower the titres of anti-HDL auto-antibodies, which are closely related to anti-apoA1 antibodies.…”
Section: Discussionmentioning
confidence: 75%